Tooth for a tooth: Tissue engineering made easy at dental chairside - Vandana Kharidhi Laxman; Rajendra Gururao Desai (Wolters Kluwer Medknow Publications, 2017)
Background: Stem cells are unspecialized, multipotent cells which can differentiate into different cell types. The human periodontal ligament encloses subpopulation of Periodontal Ligament Stem Cells (PDLSCs) which are able to regenerate the periodontium by differentiating into various cells of PDL. Literature have shown the promising results of periodontal regeneration by exvivo cultured transplantation of PDLSCs into the osseous defects. Methods: Based on current literature on use of ex vivo culture and associated problems, a novel technique is being presented , Stem cell application in periodontal regeneration (SAI-PRT) which uses autologous PDLSCs along with its niche adhering to extracted tooth root for direct application using gelatin sponge as scaffold in regeneration of intrabony periodontal defect bypassing ex-vivo culture. Results: The cases initiated under SAI-PRT protocol, and have shown excellent clinical and radiographic improvement in intrabony defect using direct transplant of autologous PDLSCs . Conclusions: SAI-PRT can be used for the treatment of periodontal osseous defects at chair side.